Novel Hilda: Image of Women Sexual Victim Violence (Gender and Feminist Study) - Ainul Luthfia Al Firda (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2022)
This study discusses the study of gender and feminism in a novel Hilda by Muyassarotul Hafidzoh. A novel that talks about the lives of survivors of sexual violence who struggle to get justice for themselves, fight trauma, and efforts to empower women within the scope of Islamic boarding schools. The purpose of this study is to analyze the study of gender and feminism in the novel Hilda, as well as to see the image of women who are victims of sexual violence. The research method used is descriptive-analytic with reference to the approach of feminism. The analytical knife used is the study of feminism and gender criticism. From the results of the study, it can be seen that Hilda is a representation of survivors of sexual violence who has experienced social discrimination, including expulsion from school, stigma, stereotypes, marginalization, violence, multiple traumas. The image of women in the figure of Hilda is depicted as a strong, intelligent character, and as a survivor of marital sexual violence, she also deserves to feel, because survivors are not unholy creatures. The image of pesantren can be categorized as an educational institution that is safe for women even in recovering past trauma by providing them with religious and social knowledge